Reversible ventricular arrythmia induced by dasatinib. Issue 1 (31st July 2013) - Spechbach, Hervé; Morel, Philippe; Lorenzini, Kuntheavy Ing; Besson, Marie; Gétaz, Laurent; Sunthorn, Henri; Chalandon, Yves
Key Clinical Message Ventricular arrhythmias induced by dasatinib are rare events, but physicians in charge of chronic myeloid leukemia patients should be aware of such potential complications and the need for regular ECG controls during treatment with tyrosine kinase inhibitors.